2020
DOI: 10.3171/2019.1.jns183157
|View full text |Cite
|
Sign up to set email alerts
|

The effect of seizure spread to the amygdala on respiration and onset of ictal central apnea

Abstract: OBJECTIVESudden unexpected death in epilepsy (SUDEP) is the leading cause of death for patients with refractory epilepsy, and there is increasing evidence for a centrally mediated respiratory depression as a pathophysiological mechanism. The brain regions responsible for a seizure’s inducing respiratory depression are unclear—the respiratory nuclei in the brainstem are thought to be involved, but involvement of forebrain structures is not yet understood. The aim of this study was to analyze intracranial EEGs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 34 publications
6
70
0
Order By: Relevance
“…Forebrain sites likely influence brainstem respiratory networks through neural projections, which might provide pathways for seizure-induced apnea. Consistent with these possibilities, recent studies indicate that loss of breathing in adult patients with epilepsy coincides with seizure spread to the amygdala (16,23). In adults, electrical stimulation of the amygdala reproduced this apnea (16,17).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 59%
“…Forebrain sites likely influence brainstem respiratory networks through neural projections, which might provide pathways for seizure-induced apnea. Consistent with these possibilities, recent studies indicate that loss of breathing in adult patients with epilepsy coincides with seizure spread to the amygdala (16,23). In adults, electrical stimulation of the amygdala reproduced this apnea (16,17).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 59%
“…Functional connectivity maps of the human amygdala confirm regional amygdala differences that correlate with histologically defined subnuclei; the lateral‐basal nuclear groups show widespread cortical connections and the centromedial groups project to regions with putative roles in arousal and autonomic regulation, including brainstem reciprocal connections . The lateral nucleus can generate spontaneous interictal activity, and ictal central apnea has been reported with seizure spread to the amygdala . In a recent study of the amygdala kindling model of epilepsy, amygdala stimulation was associated with reduced ictal ventilation and c‐fos expression in neurons in brainstem respiratory nuclei .…”
Section: Discussionmentioning
confidence: 83%
“…10 The lateral nucleus can generate spontaneous interictal activity, 38 and ictal central apnea has been reported with seizure spread to the amygdala. 5 In a recent study of the amygdala kindling model of epilepsy, amygdala stimulation was associated with reduced ictal ventilation and c-fos expression in neurons in brainstem respiratory nuclei. 39 Clinical studies have demonstrated apnea following electrode stimulation of the amygdala in people with epilepsy under investigation [6][7][8] ; apnea occurred following stimulation of the medial amygdala in one study 6 but following stimulation of lateral and basolateral nuclei in an earlier study but without lateralization.…”
Section: Regional Function Of the Amygdala And Relevance To Sudepmentioning
confidence: 99%
See 2 more Smart Citations